Validity of the Best Practice Tariff in paediatric major trauma: A retrospective cohort study from a level 1 children's major trauma centre. Issue 8 (August 2020) - Fontalis, Andreas; Nguyen, Mai Phuong; Williamson, Michael; Gabbott, Ben; Yeo, Andrea
Highlights: BPT has played a key role in universalising and standardising best practice in major trauma. Increased complexity of intervention, an increase in operative treatment and hospital stay was evident in paediatric cases qualifying for BPT. However, the stringency of the system has resulted in disproportionate reimbursement of care providers in paediatric trauma. ISS score >8 demonstrated excellent prognostic value in predicting high resource utilisation and it should remain part of the approval process. Notwithstanding, fine tuning of current qualifying criteria should be considered. Abstract: Introduction: The Best Practice Tariff (BPT) in major trauma awards Major Trauma Centres (MTCs) a financial incentive when predefined standards of care are met. However, no tailored criteria exist with regards to the reimbursement policy in paediatric major trauma. In this study, we aim to examine the utility of the paediatric Major Trauma BPT and identify predictors of additional resource utilisation. Materials and methods: This cohort study encompassed all paediatric major trauma calls ( N = 682) presenting to a designated combined adult and paediatric MTC between July 2014 and June 2017. Patient demographics, admission pattern, injury parameters, length of stay (LOS) and the need for operative management were collected. Patients approved for the BPT uplift payment (BPT group) were compared with the cohort of children not qualifying (non-BPT group). Results: Overall, less than a quarter (23.2%) of the trauma population qualified for the BPT. The proportion of patients requiring operative intervention and CT scanning in the BPT group was significantly higher ( p <0.001). These children also attained a higher ISS (median, 13.5 vs. 0, p <0.001) and required longer hospitalisation. Following a Receiver Operator Characteristic (ROC) curve analysis, a cut off ISS score > 8 demonstrated an excellent predictive value in identifying children qualifying for BPT (true positive and false positive rates: 90% and 10.7%). However, a subgroup analysis including the more severely injured children (ISS >8) not qualifying for the uplift payment revealed that equally substantial resource went into their management - 42.9% needed surgical intervention and 57.1% a CT scan. Discussion: This study demonstrated that BPT in paediatric major trauma is a valuable reimbursement; however, our findings also unveiled a cohort deemed ineligible for BPT despite the high costs accrued. Re-evaluation of the remuneration criteria of paediatric major trauma networks with an alternative, more inclusive reimbursement policy is needed.